Aplicación de las normas internacionales de información financiera para pymes para la textilera pan-pacífico comercial e industrial cía. ltda., en la provincia de Pichincha – cantón Quito – para el año 2012 - Maigua Aimacaña, Mirian Alexandra (2015)
The present work set outs International Financial Reporting Standards (IFRS) to SMEs; considering the general aspects and a research about de SMEs in Ecuador is underway; a comparative analysis of financial statements was elaborated before the aspects with the (IFRS) in the PAN-PACIFIC COMMERCIAL AND INDUSTRIAL Ltd., with the aim of demonstrating the main impacts and variations that affects the accounts that get in the financial states….